1927 N.J. Laws 743, ch. 321, § 2 - (:unkn) unknown (General Publisher, 1927)
Sentencing enhancement for possession of particular weapons while committing assault, robbery, larceny, burglary, breaking and entering. Weapons include revolvers, pistols, other firearms, blackjacks, slung-shots, billys, sandclubs, sandbags, bludgeons, metal knuckles, dagger, dirk, dangerous knife, stiletto, bomb, or other high explosive. Sentences are fixed at five, ten, and fifteen years for the first, second, and third offenses. Fourth offense is subject to life in prison.
--
Keywords: CARRY - INTENT TO COMMIT CRIME